Optimization methods for water supply SCADA system - Babunski, Darko; Zaev, Emil; Tuneski, Atanasko; Bozovic, Dejan (2018 7th Mediterranean Conference on Embedded Computing (MECO), 2018)
Drinking water reserves are not infinite natural resource. Rapid social development generates huge pollution of all of the environment, including surface and underground drinking water reserves. One of the biggest challenges in management and control of modern city water supply system is to retain uninterrupted supply with chemically and biologically safe drinking water. Real-time monitoring systems of the water quality and quantity parameters gives us on-time alert and more time for reaction. The possible solution for this challenge is presented. Real-time measuring station using industrial SCADA system and optimization of the system is recommended. SCADA system provides continuous monitoring of the many physical, chemical and biological parameters enabling fast and reliable detection of the deviations in system. Saved data give chance for additional analysis of the measured parameters and dependencies between. One possible methodology for control, reduction and optimization of water loss in the communal water supply system is recommended, with efficient usage of modern SCADA systems implemented to existing water supply systems, becoming integral part in the new optimized operational management and control system of communal water supply companies.